The Collection. - Annibaldi, Cesare; Bruno, Andrea; Cerri, Maria Grazia; Comba, Andrea; Fagiolo dell'Arco, Maurizio; Gianelli, Ida; Gritella, Gianfranco; Leo, Giampiero; Rivetti, Marco; Russo, Antonella; Verzotti, Giorgio (Rivoli : Castello di Rivoli Museo d'Arte Contemporanea, 1955)
Accardi, Carla ; Anselmo, Giovanni ; Bagnoli, Marco ; Baumgarten, Lothar ; Bianchi, Domenico ; Birnbaum, Dara ; Byars, James Lee ; Calzolari, Pierpaolo ; Castellani, Enrico ; Cattelan, Maurizio ; Charlton, Alan ; Cucchi, Enzo ; Delvoye, Wim ; Dibbets, Jan ; Fabro, Luciano ; Fontana, Lucio ; Förg, Gunther ; Gilbert & George ; Kirkeby, Per ; Lemieux, Annette ; LeWitt, Sol ; Long, Richard ; Mainolfi, Luigi ; Melotti, Fausto ; Merz, Mario ; Merz, Marisa ; Moro, Liliana ; Mullican, Matt ; Nordman, Maria ; van Bruggen, Oldenburg - ; Paolini, Giulio ; Penck, A.R. ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Salvadori, Remo ; Sieverding, Katharina ; Spalletti, Ettore ; Toroni, Niele ; Vedova, Emilio ; Vercruysse, Jan ; Verhoef, Toon ; Zorio, Gilberto ; Giacomelli, Mario ; Jodice, Mimmo
biografie, bibliografie
Engels
boek